Translation Quality of Tourism Transportation in Website of Solocity.Travel (Accuracy and Acceptability) - Rachwanti; Ika Oktaria Cahyaningrum (Faculty of Language and Literature, University of Surakarta, 2021)
The research aims to find out the translation accuracy and acceptability of tourism transportation text in solocity.travel (Indonesia – English Version). This research focuses on the analysis of the translation quality especially its accuracy and acceptability. This research is a descriptive qualitative method. Sampling technique of this research is purposive sampling. The researchers used content analysis as a technique of collecting data to analyze the tourism transportation texts and also collects the data from the questionnaire that was given to the three raters to analyze the accuracy and acceptability of the data. The results of the translation quality show that the translation of tourism transportation text in website of solocity.travel is accurate and acceptable.